The effect of prosthesis design on vibration of the reconstructed ossicular chain: a comparative finite element analysis of four prostheses - KELLY, DANIEL; Prendergast, Patrick John (Wolters Kluwer, 2003)
Hypothesis: We hypothesize that the differences in the bioacoustic performance of ossicular replacement prosthesis designs, and insertion positions, can be quantified using finite element analysis. Background: Many designs of prosthesis are available for middle ear surgery. Materials used, and the shape of the implants, differ widely. Advances in computer simulation technologies offer the possibility of replicating the in vivo behavior of the different prostheses. If this can be achieved, insight into the design attributes required for improved biofunctionality may be determined. Methods: Micro CT scanning and NMR imaging were used to obtain geometric information that was translated into a finite element model of the outer and middle ear. The forced frequency response across the hearing range of the normal middle ear was compared to the middle ear reconstructed with partial and total ossicular replacement prostheses (Xomed, Jacksonville, FL and Kurz, Dusslingen Germany). Results: The amplitude of vibration of the footplate was more similar to the normal ear when a Kurz TORP was implanted compared to when a Xomed TORP was implanted; this may be attributed to the latter?s titanium link. PORP prostheses were stiffest and had lower umbo vibrations and higher stapedial footplate vibrations. In all cases bar one the vibration of the prostheses had resonances that caused the vibration of the stapes footplate to be noticeably different from normal. Conclusion: We confirmed the hypothesis that finite element modelling can be used to predict the differences in the response of ossicular replacement prostheses. This study shows that computer simulation can potentially be used to test or optimize the vibro-acoustic characteristics of middle ear implants.
PUBLISHED
Keywords: Mechanical & Manufacturing Engineering